2014
DOI: 10.1155/2014/854391
|View full text |Cite
|
Sign up to set email alerts
|

Human Paraoxonase 1 as a Pharmacologic Agent: Limitations and Perspectives

Abstract: Human PON1 (h-PON1) is a multifaceted enzyme and can hydrolyze (and inactivate) a wide range of substrates. The enzyme shows anti-inflammatory, antioxidative, antiatherogenic, ant-diabetic, antimicrobial, and organophosphate (OP)-detoxifying properties. However, there are certain limitations regarding large-scale production and use of h-PON1 as a therapeutic candidate. These include difficulties in producing recombinant h-PON1 (rh-PON1) using microbial expression system, low hydrolytic activity of wild-type h-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 84 publications
0
9
0
Order By: Relevance
“…It is however exceptionally difficult to separate PON1 from other HDL components, such as apolipoprotein AI (apoAI) and phospholipase A2 (PLA2), without subjecting it to conditions which might affect its catalytic activity (Ben-David et al, 2015 ). Similarly, the increased polarity of recombinant PON1 would be expected to compromise its ability to hydrolyze hydrophobic substrates (Harel et al, 2004 ; Draganov et al, 2005 ; Bajaj et al, 2014 ). More lipophilic recombinant PON1 might be expected to have improved functionality, but is more difficult to isolate, a factor which will prove important in the development of recombinant PON1 for therapeutic use (Bajaj et al, 2014 ).…”
Section: Paraoxonasementioning
confidence: 99%
See 2 more Smart Citations
“…It is however exceptionally difficult to separate PON1 from other HDL components, such as apolipoprotein AI (apoAI) and phospholipase A2 (PLA2), without subjecting it to conditions which might affect its catalytic activity (Ben-David et al, 2015 ). Similarly, the increased polarity of recombinant PON1 would be expected to compromise its ability to hydrolyze hydrophobic substrates (Harel et al, 2004 ; Draganov et al, 2005 ; Bajaj et al, 2014 ). More lipophilic recombinant PON1 might be expected to have improved functionality, but is more difficult to isolate, a factor which will prove important in the development of recombinant PON1 for therapeutic use (Bajaj et al, 2014 ).…”
Section: Paraoxonasementioning
confidence: 99%
“…Similarly, the increased polarity of recombinant PON1 would be expected to compromise its ability to hydrolyze hydrophobic substrates (Harel et al, 2004 ; Draganov et al, 2005 ; Bajaj et al, 2014 ). More lipophilic recombinant PON1 might be expected to have improved functionality, but is more difficult to isolate, a factor which will prove important in the development of recombinant PON1 for therapeutic use (Bajaj et al, 2014 ). Interestingly, HDL from avian species, which lacks paraoxonase activity, does not protect human LDL against lipid peroxidation (Mackness et al, 1998 ).…”
Section: Paraoxonasementioning
confidence: 99%
See 1 more Smart Citation
“…One of the significant factors which protect serum lipids against oxidation is paraoxonase (paraoxon hydrolase; EC: 3.1.8.1; PON1) . PON1, which exhibit anti‐inflammatory and antioxidant activities, is an esterase enzyme released by the liver and related to HDL in the blood . In vivo studies, PON1 has been shown to reverse the biological effects of oxidized LDL and to protect LDL against oxidation .…”
Section: Introductionmentioning
confidence: 99%
“…We encountered a study on refolding of rhPON1. Bajaj et al 45 investigated hPON1 as a pharmacologic agent. They refolded the rh-PON1 enzyme in vitro and detected a dramatic increase in the yield of the active enzyme.…”
mentioning
confidence: 99%